2008
DOI: 10.1103/physreve.77.066601
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of traveling intrinsic localized modes in a driven electrical lattice

Abstract: The emergence of very stable traveling intrinsic localized modes (ILMs) locked to a uniform driver is demonstrated in a discrete electrical transmission line. The speed of these traveling ILMs is tunable by the driver amplitude and frequency. It is found to be quite sensitive to the ratio of intersite to on-site nonlinearity. The number of traveling ILMs can also be selected via the driving conditions and appears to be the result of a spatiotemporal pattern selection process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…In this paper we present a detailed study of discrete breathers in an electric lattice in which ILMs have been experimentally observed [15][16][17]. We propose a theoretical model which allows us to systematically study their existence, stability and properties, and to compare our numerical findings with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present a detailed study of discrete breathers in an electric lattice in which ILMs have been experimentally observed [15][16][17]. We propose a theoretical model which allows us to systematically study their existence, stability and properties, and to compare our numerical findings with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…(1) as [19,20]. Using the harmonic balance method to approximate a solution of the subharmonic response [21], such a solution assumes the form xðtÞ ¼ A 1 sinðT þ Þ þA 1=2 sinðT=2Þ þ B 1=2 cosðT=2Þ, where A 1 ¼ 1=ð1 À !…”
mentioning
confidence: 99%
“…In 1D, Ref. [16] reported detailed measurement of ILM speed. It was found that the slowest a single ILM could move in a 1D lattice of 24 nodes was 15 nodes per millisecond (15 a/ms).…”
Section: Resultsmentioning
confidence: 99%